Smectic nanostructures with typical size less than the visible light wavelength: physics and electro-optics - Pozhidaev, Evgeny Pavlovich; Molkin, Vadim Evgenievich; Chigrinov, Vladimir Grigorievich (Photonics Letters of Poland, 2011)
Very short helix pitch (p0~150-200nm) ferroelectric liquid crystals (FLCs) have been developed. Electro-optical cells based on these mixtures are free from selective reflection and diffraction in the visible spectral range and therefore exhibit very perfect operation in deformed helix ferroelectric (DHF) mode. Two main electro-optical modes of DHF cells with sub-wavelength helix pitch are under consideration Full text: PDF References: L.A. Beresnev, L.M. Blinov, D.I. Dergachev, C.B. Kondratev , "Electrooptic effect in a ferroelectric liquid crystal with a small helix pitch and a large spontaneous polarization", JETP Letters, 46(8), 328 (1987). DirectLink L.A. Beresnev, V.G. Chigrinov, D.I. Dergachev, E.P. Pozhidaev, J. Funfshilling, M. Schadt, "Deformed helix ferroelectric liquid crystal display: A new electrooptic mode in ferroelectric chiral smectic C liquid crystals", Liquid Crystals, 5(4), 1171 (1989). [CrossRef] E. P. Pozhidaev, "Electro-optical properties of deformed-helix ferroelectric liquid crystal display cells",Proc. of SPIE, 4511, 92 (2001). [CrossRef] F. Podgornov, E. Pozhidaev, D. Ganzke, W. Haase, "Variable optical attenuator based on deformed helix ferroelectric liquid crystals", Proceedings of ISAF 2000 (IEEE Catalog Number 00CH37076), 1005, (2000). [CrossRef] W. Haase, F. Podgornov, E. Pozhidaev, "Polarization-insensitive modulator based on deformed helix ferroelectric liquid crystals ", Proc. of SPIE, 4481, 17 (2002). [CrossRef] V.G. Chigrinov, H.S. Kwok, E.P. Pozhidaev, T.Z. Lu. Proc. of Second Asia-Pacific Polymer Fiber Optics Workshop, 149 (2003). W. Haase, A. Suvorova, I. Chernyaev, N. Kundikova, E. Pozhidaev, F. Podgornov, "Light Polarization Modulation with Ferroelectric Liquid Crystals", Integrated Ferroelectrics, 87, 3 (2007). [CrossRef] E.P. Pozhidaev, S.A. Pikin, D. Ganzke, S.A. Shevtchenko, W. Haase, "High frequency and high voltage mode of deformed helix ferroelectric liquid crystals in a broad temperature range", Ferroelectrics, 246, 1141 (2000). [CrossRef] I. Abdulhalim, G. Moddel, , "Electrically and Optically Controlled Light Modulation and Color Switching Using Helix Distortion of Ferroelectric Liquid Crystals ", Mol. Cryst. Liq. Cryst., 200, 79 (1991). [CrossRef] E. Pozhidaev, S. Torgova, M. Minchenko, C. A. R. Yednak, A. Strigazzi, E. Miraldi, "Phase modulation and ellipticity of the light transmitted through a smectic C* layer with short helix pitch ", Liquid Crystals, 37(8), 1067, (2010). [CrossRef] V.G. Chigrinov, Liquid Crystal Devices: Physics and Applications, Artech House, Boston, London, (1999). N.A.Clark, S.T. Lagerwall, "Submicrosecond bistable electro?optic switching in liquid crystals ", Appl. Phys. Lett. 36, 899 (1980). [CrossRef]